After single-lung transplantation volume reduction to treat native lung emphysematous hyperinflation: report of two cases - Pêgo-Fernandes, Paulo Manuel; Samano, Marcos Naoyuki; Junqueira, Jader Joel Machado; Caramoni, Marlova; Teixeira, Ricardo Henrique de Oliveira Braga; Afonso Júnior , José Eduardo; Jatene, Fabio Biscegli (Brazilian Journal of Transplantation, 2006)
Native lung hyperinflation is commonly seen next to single-lung transplant due to emphysema. The progressive graft compression by hyperinflation causes mediastinal shift and deterioration of the pulmonary function. Upon such situation, the surgical treatment consists in a volumetric reduction of the native lung. This work reports two cases of acute and late native lung hyperinflation after single-lung transplant with progressive pulmonary dysfunction, non-responsive to clinical treatment. In acute case, it was performed a lung volume reduction surgery with multiple wedge resections by surgical staplers, removing 20% of the pulmonary parenchyma. In chronic cases, it was performed an inferior lobectomy, because of the results of the cintilography.